Detection of protein similarities using nucleotide sequence databases. - Henikoff, S.; Wallace, J.C. (Nucleic Acids Research, 1988)
A simple procedure is described for finding similarities between proteins using nucleotide sequence databases. The approach is illustrated by several examples of previously unknown correspondences with important biological implications: Drosophila elongation factor Tu is shown to be encoded by two genes that are differently expressed during development; a cluster of three Drosophila genes likely encode maltases; a flesh-fly fat body protein resembles the hypothesized Drosophila alcohol dehydrogenase ancestral protein; an unknown protein encoded at the multifunctional E. coli hisT locus resembles aspartate beta-semialdehyde dehydrogenase; and the E. coli tyrR protein is related to nitrogen regulatory proteins. These and other matches were discovered using a personal computer of the type available in most laboratories collecting DNA sequence data. As relatively few sequences were sampled to find these matches, it is likely that much of the existing data has not been adequately examined.